A Review Paper on Stock Market Analysis (International Journal of Innovative Research in Engineering & Management, 2021)
Stock market forecasting has long  piqued the curiosity of analysts and academics. Stock  markets, according to common thinking, are essentially  random walks, and trying to predict them is a fool's game.  Predicting stock prices is a tough endeavor in and of itself  due to the many variables involved. In the short term, the  market works like a voting machine, but in the long run, it  works like a weighing machine, allowing for the prediction  of market movements over a longer period of time.  Machine learning and other algorithms may be used to  assess and forecast stock values, and this is an area with a  lot of promise. In this article, we begin with a quick review  of stock markets and a taxonomy of stock market  prediction approaches. The focus changes to some of the  scientific achievements in stock analysis and forecasting  after that. We go through stock analysis approaches such  as technical, fundamental, short-term, and long-term. Finally, we go through some of the field's challenges and  research opportunities.
Keywords: Stock Exchanges; Stock Markets; Analysis; Prediction